Phase competition driven temperature broadening of colossal magnetoresistance in La0.815Sr0.185MnO3 - Pattabiraman M.; Adepu R.; Singh N.P.; Venkatesh R.; Angappane S.; Rama N.; Rangarajan G. (My University, 2025)
It is shown that the temperature dependence of the magnetoresistance (MR) in manganites can be appreciably broadened by enhancing phase competition. By substituting Mn4+ with small amounts of Ti4+, the ferromagnetic metallic La0.815Sr0.185MnO3 is pushed closer to the ferromagnetic metallic (FMM)/ferromagnetic insulating (FMI) phase boundary. Ti4+ substitution significantly reduces the ferromagnetic and insulator-metal transition temperatures and broadens their evolution. This results in weak temperature dependence of the MR across the M-I transition with a variation of only about 0.5%. Thus, the route adopted is well suited for overcoming one of the major limitations of using colossal magnetoresistive manganites as magnetosensitive devices. © 2006 Elsevier B.V. All rights reserved.